King Seneb-Kay's tomb and the necropolis of a lost dynasty at Abydos - Wegner, Josef W. (University Museum monograph, 2021)
Frontmatter -- Contents -- Figures -- Tables -- Contributors -- Acknowledgments -- Glossary of Place Names and Terms -- Part 1: The Tomb of King Woseribre Seneb-Kay -- Introduction -- 1. Excavation And Architecture of the Tomb of Seneb-Kay -- 2. The Burial Chamber -- 3. The Funerary Equipment -- 4. The Canopic Chest -- 5. Osteobiography of Woseribre Seneb-Kay -- 6. Conservation and Restoration Work -- Part 2: The Reused Material in the Tomb of Seneb-Kay -- 7. The Reused Roof Blocks -- 8. The Reused 13th Dynasty Chapel Blocks -- 9. Chapel Architecture Commemorating Ibiau and Dedtu -- 10. The Family History of Dedtu and Ibiau -- Part 3: The Main Tomb Cluster -- 11. Excavation and Architecture of the Tombs -- 12. Architectural Traditions in the Second Intermediate Period -- 13. The Skeletal Remains from the Main Tomb Cluster -- Part 4: Historical and Archaeological Synthesis -- 14. Seneb-Kay and the Abydos Dynasty -- 15. The Archaeology of Political Dissonance in Egypt’s Second Intermediate Period -- References